The islamic panacea to global financial predicament:a new financial architecture - Masudul Alam Choudry (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
The roots of the 2008 global financial crisis that originated in the United States subprime mortgage market are firstly traced to the demand side of financing. Borrower preferences are explained to be based on excessiveness of ownership and spending. Such excessive consumer preferences are matched up with the suppliers’ decision to allow easy lending and accumulation of multiple debt-ridden loans. The cost of such financial excessiveness is shown to be the rate of interest. The relevance of interest rate in efficient financing and economic resource mobilization is questioned here from the theoretical side. Its rejection and replacement by participatory financing instruments in the good things of life is formalized. A new financial architectural design is thus laid out in terms of the central issue of money, finance and real economy complementary relations. These relations can be simulated by circular causation equations. The foundational conceptual premise is governed by the episteme of unity of knowledge. Thus the Islamic worldview of unity of knowledge is invoked to address the theme of 100% Reserve Requirement Monetary System (100%RRMS). Its social and economic implications are formalized